2008
DOI: 10.1103/physrevc.78.054315
|View full text |Cite
|
Sign up to set email alerts
|

Lowest order constrained variational calculation of polarized neutron matter at finite temperature

Abstract: Some properties of the polarized neutron matter at finite temperature has been studied using the lowest order constrained variational (LOCV) method with the AV 18 potential. Our results indicate that spontaneous transition to the ferromagnetic phase does not occur. Effective mass, free energy, magnetic susceptibility, entropy and the equation of state of the polarized neutron matter at finite temperature are also calculated. A comparison is also made between our results and those of other many-body techniques.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
1
28
1
Order By: Relevance
“…Such an attempt was made in the recent article [59] by attracting the ideas from the nuclear energy density functional theory. However, the constraints obtained in this study on the Skyrme force parameters lead to the unrealistic consequence that the effective masses of nucleons with spin up and spin down in a polarized state should be equal, contrary to the results of calculations with realistic NN interaction [29,31]. On the other hand, the observational data still do not rule out the existence of a ferromagnetic hadronic core inside a neutron star caused by spontaneous ordering of hadron spins (in this respect, see, e.g., Refs.…”
Section: Unusual Behavior Of the Entropy At H =contrasting
confidence: 68%
See 1 more Smart Citation
“…Such an attempt was made in the recent article [59] by attracting the ideas from the nuclear energy density functional theory. However, the constraints obtained in this study on the Skyrme force parameters lead to the unrealistic consequence that the effective masses of nucleons with spin up and spin down in a polarized state should be equal, contrary to the results of calculations with realistic NN interaction [29,31]. On the other hand, the observational data still do not rule out the existence of a ferromagnetic hadronic core inside a neutron star caused by spontaneous ordering of hadron spins (in this respect, see, e.g., Refs.…”
Section: Unusual Behavior Of the Entropy At H =contrasting
confidence: 68%
“…It was shown that the behavior of spin polarization of neutron matter in the high density region in a strong magnetic field crucially depends on whether neutron matter develops a spontaneous spin polarization (in the absence of a magnetic field) at several times nuclear matter saturation density, or the appearance of a spontaneous polarization is not allowed at the relevant densities (or delayed to much higher densities). The first case is usual for the Skyrme forces [13][14][15][16][17][18][19][20][21][22][23], while the second one is characteristic for the realistic nucleon-nucleon (NN) interaction [24][25][26][27][28][29][30][31][32]. In the former case, a ferromagnetic transition to a totally spin polarized state occurs while in the latter case a ferromagnetic transition is excluded at all relevant densities and the spin polarization remains quite low even in the high density region.…”
Section: Introductionmentioning
confidence: 99%
“…In our calculations, the equation of state of hot nucleonic matter is determined using the lowest order constrained variational (LOCV) method as follows [9][10][11][12][13][14][15][16]. We adopt a trail wave function as…”
Section: A Hadron Phasementioning
confidence: 99%
“…It has been seen that the critical temperature for the CDBONN potential in the BHF approximation (T c ≃ 23.3 MeV ) is larger than the critical temperature for the same potential but in the Self-Consistent Greens Functions approach (SCGF) (T c ≃ 18.5 MeV ) [12]. In this reference, it has also been shown that for AV 18 potential, the critical temperature is lower than for the CDBONN potential [12]. Employing the self-consistent Hartree-Fock approach using different mean-field interactions of the Skyrme and the Gogny types, it has been indicated that the critical temperatures span a wide range of values, from T c ≃ 14 to 23 MeV showing the effective interaction dependence of the critical properties [13].…”
Section: Introductionmentioning
confidence: 91%
“…In fact, we use a quadratic approximation for the single particle potential incorporated in the single particle energy as a momentum independent effective mass. We introduce the effective masses, m * (i) j , as variational parameters [7,18]. We minimize the free energy with respect to the variations in the effective masses and then we obtain the chemical potentials and the effective masses of the spin-up and spin-down nucleons at the minimum point of the free energy.…”
Section: Finite Temperature Calculations For Spin Polarized Nu-clmentioning
confidence: 99%